WOMEN SCHOLARS AND THE FORMATION OF ACADEMIC CULTURE, ETHICAL LEADERSHIP, AND SOCIAL PROGRESS (World Conference on Social Sciences, Law and Public Policy, 2026)
This article explores the role of women scholars in the development of academic culture, ethical leadership, and social progress in contemporary society. Unlike approaches that focus mainly on women’s participation in STEM or technological innovation, this study emphasizes the cultural, pedagogical, ethical, and social dimensions of women’s scientific activity. Women scholars are considered not only as producers of scientific knowledge, but also as mentors, educators, public intellectuals, and agents of social transformation. The article argues that the presence of women in science strengthens academic responsibility, enriches research culture, promotes inclusive education, and contributes to the formation of a more humane and intellectually mature society. The study also highlights the importance of institutional support, mentoring systems, gender-sensitive academic environments, and the public recognition of women’s scientific achievements.
Keywords: women scholars, academic culture, ethical leadership, social progress, higher education, mentorship, gender equality, scientific responsibility, inclusive education.